Characteristics of Effective School Principals: A Mixed-Research Study - Schulte, Don P.; Slate, John R.; Onwuegbuzie, Anthony J. (Alberta Journal of Educational Research, 2010)
In this multi-stage mixed analysis study, the views of 615 college students enrolled at two Hispanic-serving institutions in the Southwest were obtained concerning characteristics of effective school principals. Through the method of constant comparison (qualitative phase), 29 dominant themes were determined to be present in respondent-identified characteristics of effective school principals: Leader, Communication, Caring, Understanding, Knowledgeable, Fair, Works Well With Others, Listening, Service, Organized, Disciplinarian, Good Attitude, Patience, Respectful, Helping, Open-Mindedness, Motivating, Professional, Flexible, Being Visible, Honest, Good Role Model, Responsible, Builds Relationships, Involving, Consistent, Friendly, Focus on Schools, and Experience in the Classroom. An exploratory factor analysis revealed that these 29 themes represented five meta-themes. Then these themes (quantitative phase) were converted into numbers (i.e., quantitized) into an interrespondent matrix that consisted of a series of 1s and 0s and were analyzed to determine whether participants’ themes differed as a function of sex, ethnicity, college status, and first-generation/non-first-generation status. Statistically significant differences were present between undergraduate and graduate students, between males and females, between Hispanics and Whites, and between first-generation and non-first-generation college students. Implications are discussed.